1997
DOI: 10.1093/emboj/16.16.5037
|View full text |Cite
|
Sign up to set email alerts
|

Adjacent DNA elements dominantly restrict the ubiquitous activity of a novel chromatin-opening region to specific tissues

Abstract: Locus control regions (LCRs) are thought to provide a dominant tissue‐specific open chromatin domain that allows for proper gene regulation by enhancers/silencers and their associated transcription factors. Expression of the T‐cell receptor alpha (TCRα) gene is limited to T cells and its locus exists in different chromatin configurations in expressing and non‐expressing cell types. Here we show that eight DNase I‐hypersensitive sites in the TCRα locus comprise an LCR that confers T‐cell compartment‐specific ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
81
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(85 citation statements)
references
References 54 publications
(114 reference statements)
3
81
1
Order By: Relevance
“…The construction of the 9-kb HS1-8 fragment, 5.9-kb HS2-6 fragment, and the ␤:1-8 and ␤:2-6 transgenes have all been previously described (14). For the ␤:6 construct, a 1.6-kb MfeI/SacI fragment of the HS1-8 region was excised from the pSP72:HS1-8 vector.…”
Section: Dna Constructsmentioning
confidence: 99%
See 3 more Smart Citations
“…The construction of the 9-kb HS1-8 fragment, 5.9-kb HS2-6 fragment, and the ␤:1-8 and ␤:2-6 transgenes have all been previously described (14). For the ␤:6 construct, a 1.6-kb MfeI/SacI fragment of the HS1-8 region was excised from the pSP72:HS1-8 vector.…”
Section: Dna Constructsmentioning
confidence: 99%
“…Four independent lines of ␤:6 and five lines of ␤:⌬6 transgenic mice were generated and analyzed. These lines were compared with lines of ␤:2-6 mice that were generated and described previously (14) to determine the sequences contributing to the activity of the HS2-6 region.…”
Section: Deletion Analysis Of the Hs2-6 Region Of The Tcr␣ Lcrmentioning
confidence: 99%
See 2 more Smart Citations
“…The TCR § chain control elements have been well defined, and the pT § cassette contains the 3' TCR § enhancer and most of the TCR § LCR (locus control region), including DNase hypersensitivity sites (HS) 7, 8, 1, 1', 2, and 3 (in 5'-3' order), but lacks HS4, 5 and 6 [22,23]. Deletional analysis of TCR § LCR demonstrated that HS1, which overlaps with the TCR § enhancer, was important for high-level expression of a reporter gene in thymus, but not in the spleen, and that it was not critical for tissue specific chromatin opening [24,25]. Further deletion of HS1' diminished tissue-specific control of chromatin-opening gene expression of genes proximal to TCR § LCR.…”
Section: Discussionmentioning
confidence: 99%